Program â€œCERDIKâ€ Meningkatkan Perilaku Pencegahan Hipertensi Pada Penderita Usia 45-54 Tahun - Kamila, Adzkia Zahra; Vidyarini, Andra; Furqan, Mohammad (JURNAL RISET GIZI, 2024)
Background: In Indonesia, there is an increasing prevalence of hypertension in the 45-54 age group. This degenerative disease has a significant impact with high morbidity and mortality rates, and affects the quality of life of sufferers. Hypertension can increase the risk of developing cardiovascular disease, coronary heart disease, stroke, kidney damage and diabetes mellitus. The "CERDIK" programme which includes regular health check-ups, smoking cessation, physical activity, a balanced diet, adequate rest, and stress management are good measures to prevent and control high blood pressure.Objective: To determine the relationship between knowledge and "CERDIK" behaviour with hypertension in 45-54 years old at UPTD Puskesmas Jatisampurna, Bekasi city.Methods: This study used a cross-sectional study design with purposive sampling technique. The population in this study were hypertensive patients aged 45-54 years at the UPTD Puskesmas Jatisampurna, Bekasi city. The sample in this study totalled 66 respondents. Data were analysed using the chi square test. Results: The results showed that there was no significant relationship between CERDIK knowledge (P value = 0.300 > 0.05) and hypertension and there was a significant relationship between CERDIK behaviour (P value = 0.007 < 0.05) and hypertension.Conclusion: The study shows that there is an association between CERDIK behaviour and hypertension